English Fun Quest: Learning Assistance Program through Fun Games to Improve Students' English Language Skills in the Campus Environment - Fikri, Moh. Hilman; Wahyuni, Sri; Pahlevi, Muhammad Rizza; Yasin, Mohammad Ilham; Sudrajad, Wahyu; Iman Jauhari; Gigih Dwi Ananto (⁠International Journal of Asia Pacific Community Service, 2024)
Anxiety plays a big role in impeding students to speak. Thus, the current community service aims to enhance the students’ confidence and speaking skills to speak English. The activity recruited all fresh semester students of Cipta Wacana Christian University. Vocabulary building games (flash cards, role playing games, interactive story telling), language workshop, peer mentoring, and online platforms were implemented in the study. The results unpacked that the activities may significantly ameliorate the students’ confidence and speaking ability. Moreover, one of the students depicted that he went to a Sunday market to look for a native speaker and practice his speaking skills, implying the significance impact of the program. Finally, the authors wish that the program can be upgraded to achieve English holistic learning.